Late Quaternary Fault Slip Rate Within the Qilian Orogen, Insight Into the Deformation Kinematics for the NE Tibetan Plateau. Issue 5 (6th May 2021) - Hu, Xiaofei; Cao, Xilin; Li, Tao; Mao, Junwei; Zhang, Jian; He, Xin; Zhang, Ya'nan; Pan, Baotian
Abstract: Various kinematic models have been proposed to explain the growth process of wide compressive orogens, and the deformation rate within the entire range of the orogen (rather than that of the leading‐edge fault) provides valuable information for model evaluation. Within the Qilian Orogen, between the central and northern Qilian Shan mountain in China, we studied the deformation of a series of Quaternary fluvial terraces across the North Tuolai Shan Fault (NTF), including optically stimulated luminescence dating of terrace ages. The results show that the six levels of terraces (T6 to T1) were formed at 58.4 ± 4.4 ka, 53 ± 5 ka, 46 ± 5 ka, 38 ± 5 ka, 23.2 ± 1.8 ka, and 4.8 ± 0.4 ka, respectively. Field investigations revealed that these terrace surfaces are faulted and folded by the NTF. Based on the deformation and ages of the terraces across the fault, the vertical slip rate is estimated as 1.5 ± 0.1 mm/yr, and the shortening rate is 0.9 ± 0.1 mm/yr, with a fault dip of 58°–60°. This deformation rate is similar to rates determined along the leading‐edge fault in the northern Qilian Shan and along the fault in the southern Qilian Shan. The widely distributed shortening across the ∼300‐km‐wide Qilian Orogen supports the kinematics of distributed upper crustal shortening across the Qilian Orogen, with a ductile lower crust, rather than a large, gradually propagating crustal‐scale deformation wedge. Key Points: The shortening rate across the North Tuolai Shan Fault is estimated as 0.9 mm/yr, based on optically stimulated luminescence dating of fluvial terraces The shortening rate within the ∼300 km Qilian Orogen suggests that crustal shortening is widely distributed along several thrust belts The distributed shortening supports the kinematics of a distributed upper crustal shortening across the orogen, with a ductile lower crust